Effects of resistance training in children and adolescents: A meta-analysis - Behringer, M.; vom Heede, A.; Yue, Z.; Mester, J. (Pediatrics, 2010)
Although physiologic benefits of resistance training for children and adolescents have been well documented, the impact of age and maturity on trainability of muscle strength remains poorly understood. OBJECTIVE: To assess the effects of resistance training in different age groups and maturity levels. METHODS: We searched electronic bibliographic databases, key journals, and reference lists of reviews, book chapters, and articles. Two independent reviewers evaluated the effects of resistance training on muscle strength for prepubertal and postpubertal healthy children and adolescents (younger than 18 years) by using the results of randomized and nonrandomized controlled trials. Assessments of muscle endurance and motor performance tests (eg, vertical jump) were excluded. The influence of continuous and categorical moderator variables was assessed by meta-regression and subgroup analyses, respectively. RESULTS: The overall weighted effect size of 1.12 (95% confidence interval: 0.9 -1.3) was significantly greater than 0 (P .01). Subgroup analyses revealed "maturity" to be a significant categorical moderator variable (z 2.50; P .01) and positive correlation coefficients were found for the continuous variables "duration" (r 0.28; P .02) and "frequency" (r 0.26; P .03). CONCLUSIONS: The results of our analysis indicate that the ability to gain muscular strength seems to increase with age and maturational status, but there is no noticeable boost during puberty. Furthermore, study duration and the number of performed sets were found to have a positive impact on the outcome